Weed interference in maize, cowpea, maize/cowpea intercrop in a subhumid tropical environment. I. Influence of cropping season - Ayeni, A.O.; Duke, W.B.; Akobundu, I.O. (1984)
Field experiments were conducted in the early and late cropping seasons of 1979 on a loamysand Oxic Ustropept in a subhumid environment in Nigeria, using 40000, 50000 and 30000 + 40000 plants ha−1 of maize (Zea mays L. cv. TZB), cowpea (Vigna unguiculata (L.) Walp. cv. VITA‐5) and maize/cowpea intercrop respectively. These indicated that weed interference effects on crops under no‐tillage depended on cropping season, cropping pattern and crop species. In the early and late seasons respectively, thirty‐five and twenty‐nine different weed species were recorded and weed dry weights of approximately 10·4 and 5·7 t ha−1 from the plots kept weedy throughout the season reduced corresponding food energy yields by 60 and 82%. Except for the intercrop, which in the early season showed significant yield reduction when exposed to 4 weeks’ weed interference after sowing, all cropping patterns needed more than 4 weeks’ interference to show significant yield reductions, regardless of cropping season. In the early season, weed interference accounted more for the yield reductions in monocultures than it did for those in the intercrop, but in the late season all cropping patterns were equally sensitive to weed association. Maize, which performed much better in the early season, showed greater yield reductions than cowpea under early weed interference but less under full‐season interference irrespective of cropping pattern and season. Cowpea seed quality was more reduced by intercropping than by weed interference in the early season but neither of these factors affected seed quality significantly in the late season.